Awareness of Physiotherapy Intervention in CA-breast (Medico Legal Update, 2020)
Introduction: Physiotherapy is a healthcare profession that assesses, diagnoses, treats and works to preventdiseases and disability. Physiotherapy is a part of primary health care system. Every person has right to accessto primary health care services. Physiotherapy has an important role in various illness and disorders butpeople are less aware about its benefits. Amongst these various diseases one is breast cancer. Physiotherapyhas important role in treating the complications of Ca-breast. However there is limited research available onawareness of Physiotherapy intervention on post-operative Ca-Breast.Objective: To find the awareness of physiotherapy intervention in post-operative CA-Breast.To find awareness of Physiotherapy among Doctors.To find out the number of post-operative Ca-Breast subjects referred to Physiotherapy.To find the awareness of Physiotherapy intervention in post-operative Ca-Breast among medical doctors.Material and Methodology: Total 120 doctors were included in survey. The questionnaire were self- devisedpre validated. A survey were conducted with clinical doctors. Questions were closed ended to prevent anystatistical error.Result: In this survey we found that there are 50 percent doctors who are aware about physiotherapy and 50percent are aware about physiotherapy intervention in individuals with Ca-breast.Conclusion: The study on Awareness of Various Aspects of Physiotherapy among Medical Residents. In thisstudy identified a need for physiotherapists to educate medical residents about various fields of physiotherapylike community based rehabilitation and industrial health physiotherapy, their extensive role in each of thespecialty, treatment modalities and evaluative procedures through continuing education programs.